2011
DOI: 10.1089/acm.2010.0473
|View full text |Cite
|
Sign up to set email alerts
|

The Antiplatelet Activity of Camel Urine

Abstract: Camel urine has potent antiplatelet activity against ADP-induced (clopidogrel-like) and AA-induced (aspirin-like) platelet aggregation; neither human nor bovine urine exhibited such properties. These novel results provide the first scientific evidence of the mechanism of the presumed therapeutic properties of camel urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 20 publications
1
31
0
2
Order By: Relevance
“…The religious aspect of using camel urine stems from the fact that there has been convincing evidence that the Prophet Mohamed advised its use in the treatment of a wide range of diseases (Alhaidar et al, 2011). Anecdotal records of the management of many diseases, ranging from liver cirrhosis to skin and hair ailments, with the use of camel urine have been discovered (Christy, 1994).…”
Section: Traditional and Religious Background Of Camel Urine Usagementioning
confidence: 99%
See 3 more Smart Citations
“…The religious aspect of using camel urine stems from the fact that there has been convincing evidence that the Prophet Mohamed advised its use in the treatment of a wide range of diseases (Alhaidar et al, 2011). Anecdotal records of the management of many diseases, ranging from liver cirrhosis to skin and hair ailments, with the use of camel urine have been discovered (Christy, 1994).…”
Section: Traditional and Religious Background Of Camel Urine Usagementioning
confidence: 99%
“…Both camel plasma and urine show repression reactions on human platelets; in particular, lactating camel urine exhibits a strong repression reaction on human platelet aggregation (Alyahya et al, 2016). It has been observed that the strong platelet blocking characteristics of camel urine are quite like the reactions of commonly used antiplatelet drugs, such as clopidogrel and aspirin (Alhaidar et al, 2011).…”
Section: Cardiovascular Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Al-Abdalall [3] , proved that camel urine at low concentrations had no significant inhibitory effect on fungal growth, while inhibition can be obviously recorded after using high concentrations. Moreover, camel urine has been proved to have a potent antiplatelet activity against adenosine diphosphateinduced and arachidonic acid induced platelet aggregation; neither human nor bovine urine exhibited such properties [4] .…”
mentioning
confidence: 99%